A potential new sea surface temperature proxy based on isomeric highly branched isoprenoid lipid biomarkers: EZ25 - Belt, Simon T.; Smik, Lukas; Husum, Katrine; Knies, Jochen (Organic Geochemistry, 2025)
Two tri-unsaturated and isomeric (E/Z) highly branched isoprenoid (HBI) diatom lipid biomarkers were quantified in 228 water column samples collected from the English Channel, West Svalbard (Arctic), the Scotia Sea (Southern Ocean) and East Antarctica. We found that the relative amounts of the two HBIs correlate well with water temperatures taken at the time of sampling. Based on these findings and some other HBI data reported previously, we suggest that the proportion of the HBI E-isomer (termed EZ25) may serve as a new proxy for palaeo sea surface temperatures, including in the polar regions. Next steps will involve determination of EZ25 in surface and downcore sediments to ascertain whether the temperature response described herein translates well to the geological record.
Article number: 105056
Keywords: Scotiahavet; Sørishavet; biogeokjemi; biomarkører; geologi; paleontologi; polarområdene

Abundance and Diversity of Aerobic Anoxygenic Phototrophic Bacteria in Polar Plant Microbiomes - Mäkinen, Emilia A.; Franz, Ole; Ihalainen, Janne A.; Helander, Marjo; Nissinen, Riitta; Mathew, Suni A.; Saloniemi, Irma; Saikkonen, Kari (Physiologia Plantarum, 2025)
ABSTRACT Here, we examined the occurrence of plant-associated aerobic anoxygenic phototrophic bacteria (AAPB) across polar regions. Recently found in polar soils and cold-climate plants, AAPBs are photoheterotrophs that rely on environmental organic carbon but capture solar energy via anoxygenic photosynthesis. We revealed the abundance of AAPBs by extracting bacteria from plant tissues and imaging the colonies with bacteriochlorophyll-based near-infrared fluorescence. The taxonomic distribution of AAPBs was determined via 16S rRNA gene analysis. From the northern hemisphere, we describe AAPBs from the leaf endo- and phyllospheres of numerous sub- and Arctic plant species in Northern Finland, Svalbard, and Greenland. In the southern hemisphere, we focused on AAPBs in the root and leaf endospheres and the phyllospheres of Deschampsia antarctica in Chilean Patagonia and maritime Antarctica. Additionally, we describe AAPB from the tissues of several other plant species in Patagonia. We found AAPBs commonly associated with the sampled plant species across both hemispheres. A diversity of Alphaproteobacteria was found to contain the AAP capability: at all sampling sites, Sphingomonas was the most abundant taxon (up to 60%), while Methylobacteria made up a notable proportion of sub-Arctic and sub-Antarctic AAPB samples (up to 32%). In contrast to previous studies describing Methylobacteria frequently in various plant communities, AAP-containing Methylobacteria were virtually absent from our high-latitude sites. With diverse AAPB taxa found ubiquitously across polar regions and plant tissues, our results call attention to the potential ecological interaction between AAPBs and their plant hosts.
Publisher: John Wiley & Sons, Ltd
Keywords: Antarktis; biodiversitet; biogeografi; biologi; mikroorganismer; polarområdene

Editorial: Microplastics and nanoplastics in polar areas: Arctic, Antarctica, and the world’s glaciers - Corami, Fabiana; Iannilli, Valentina; Hallanger, Ingeborg G. (Frontiers in Marine Science, 2025)
Plastic particles are present in biotic and abiotic matrices; hence, plastic pollution is a global issue involving terrestrial and marine fauna and poses a threat to humans. Ocean circulation is a crucial vector of microplastics worldwide. Plastic pollution is among the significant threats to the ocean ecosystem. Studies and papers on plastic pollution in the oceans worldwide have been reported. However, the distribution, characterization, and abundance of micro- and nano plastics in the global ocean still need to be carefully investigated. Once plastics are present in the environment, they denature, degrade, and are more prone to fragmentation. It is well established that large plastic objects and macroplastics fragment into mesoplastics and large microplastics through photodegradation and weathering. Hence microplastics easily break up into fragments <100 µm (small microplastics, SMPs) or even into sub-micrometric particles, the nanoplastics. The small size of these SMPs and nanoplastics allows them to be ingested by different organisms according to their mouthparts’ size. Besides, this fragmentation will enable additives and plasticizers to be released into the environment, where they may pose a threat to biota throughout the trophic web in various ecosystems, e.g., from oceans and soils to glaciers. Micro- and nanoplastics (MNPs) can be transported over long distances, together with the other airborne particles. As a result of long-range transport and short-range transport, airborne MNPs can be carried from worldwide to mountain glaciers; from mid-latitudes, they can reach the very high and very low latitudes, i.e., the Arctic and Antarctica. Due to global climate change, warm ocean streams heavily affect the sea circulation in polar areas, carrying regulated and emerging pollutants, microplastics being among them. In this scenario, polar environments may be significantly enriched by MNPs carried by warmer ocean currents intruding into the polar oceans and those in atmospheric aerosol. MNPs may threaten the sea ice formation and enhance the melting of glaciers. The melting and disappearance of glaciers and the intrusion of warm currents into polar areas are also compounded by the thawing of permafrost, which can release pollutants, including MNPs. This Research Topic aims to study the interconnected pathways of MNPs that are paramount to understanding the global microplastic cycle and how climate change alters polar environments and the rest of the world. Furthermore, we aim to identify bioindicators in marine species, populations, and ecosystems, while acknowledging the interconnectedness of freshwater, terrestrial and atmospheric environments to the polar environment. Research on world glaciers will provide a comprehensive evaluation of the impacts of plastic pollution on the marine polar environment and biota, including impacts on humans.
Article Number: 1587557
Keywords: Antarktis; forurensning; isbreer; klimaendringer; mikroplast; miljøgifter; polarområdene; økologi; økosystemer

Using a multi-layer snow model for transient paleo-studies: surface mass balance evolution during the Last Interglacial - Hoang, Thi-Khanh-Dieu; Quiquet, Aurélien; Dumas, Christophe; Born, Andreas; Roche, Didier M. (Clim. Past, 2025)
During the Quaternary, ice sheets experienced several retreat–advance cycles, strongly influencing climate patterns. In order to properly simulate these phenomena, it is preferable to use physics-based models instead of parameterizations to estimate the surface mass balance (SMB), which strongly influences the evolution of the ice sheet. To further investigate the potential of these SMB models, this work evaluates the BErgen Snow SImulator (BESSI), a multi-layer snow model with high computational efficiency, as an alternative to providing the SMB for the Earth system model iLOVECLIM for multi-millennial simulations as in paleostudies. We compare the behaviors of BESSI and insolation temperature melt (ITM), an existing SMB scheme of iLOVECLIM during the Last Interglacial (LIG). Firstly, we validate the two SMB models using the regional climate model Mod- èle Atmosphérique Régional (MAR) as forcing and reference for the present-day climate over the Greenland and Antarctic ice sheets. The evolution of the SMB over the LIG (130–116 ka) is computed by forcing BESSI and ITM with transient climate forcing obtained from iLOVECLIM for both ice sheets. For present-day climate conditions, both BESSI and ITM exhibit good performance compared to MAR despite a much simpler model setup. While BESSI performs well for both Antarctica and Greenland for the same set of parame- ters, the ITM parameters need to be adapted specifically for each ice sheet. This suggests that the physics embedded in BESSI allows better capture of SMB changes across varying climate conditions, while ITM displays a much stronger sen- sitivity to its tunable parameters. The findings suggest that BESSI can provide more reliable SMB estimations for the iLOVECLIM framework to improve the model simulations of the ice sheet evolution and interactions with climate for multi-millennial simulations.
Publisher: Copernicus Publications
Keywords: Antarktis; innlandsis; klimamodeller; paleoklimatologi; polarområdene

Community estimate of global glacier mass changes from 2000 to 2023 - Zemp, Michael; Jakob, Livia; Dussaillant, Inés; Nussbaumer, Samuel U.; Gourmelen, Noel; Dubber, Sophie; A, Geruo; Abdullahi, Sahra; Andreassen, Liss Marie; Berthier, Etienne; Bhattacharya, Atanu; Blazquez, Alejandro; et al. (Nature, 2025)
Glaciers are indicators of ongoing anthropogenic climate change1. Their melting leads to increased local geohazards2, and impacts marine3 and terrestrial4,5 ecosystems, regional freshwater resources6, and both global water and energy cycles7,8. Together with the Greenland and Antarctic ice sheets, glaciers are essential drivers of present9,10 and future11–13 sea-level rise. Previous assessments of global glacier mass changes have been hampered by spatial and temporal limitations and the heterogeneity of existing data series14–16. Here we show in an intercomparison exercise that glaciers worldwide lost 273 ± 16 gigatonnes in mass annually from 2000 to 2023, with an increase of 36 ± 10% from the first (2000–2011) to the second (2012–2023) half of the period. Since 2000, glaciers have lost between 2% and 39% of their ice regionally and about 5% globally. Glacier mass loss is about 18% larger than the loss from the Greenland Ice Sheet and more than twice that from the Antarctic Ice Sheet17. Our results arise from a scientific community effort to collect, homogenize, combine and analyse glacier mass changes from in situ and remote-sensing observations. Although our estimates are in agreement with findings from previous assessments14–16 at a global scale, we found some large regional deviations owing to systematic differences among observation methods. Our results provide a refined baseline for better understanding observational differences and for calibrating model ensembles12,16,18, which will help to narrow projection uncertainty for the twenty-first century11,12,18.
Keywords: Antarktis; fjernmåling; glasiologi; havnivåstigning; hydrologi; isbreer; klimaendringer; kryosfæren; polarområdene

A virtual geobibliography of polar tourism and climate change - Demiroglu, O. Cenk; Bohn, Dorothee; Dannevig, Halvor; Hall, C. Michael; Hehir, Christy; Lundmark, Linda; Nilsson, Robert O.; Olsen, Julia; Tervo-Kankare, Kaarina; Vereda, Marisol; Welling, Johannes (Journal of Sustainable Tourism, 2024)
The polar regions are increasingly at the center of attention as the hot spots of climate crisis as well as tourism development. The recent IPCC reports highlight several climate change risks for the rather carbon-intensive and weather-based/dependent polar tourism industry in the Arctic and the Antarctic. This study presents the scholarly state-of-knowledge on tourism and climate change in the polar regions with a literature survey extending beyond the Anglophone publications. As a supporting tool, we provide a live web GIS application based on the geographical coverages of the publications and filterable by various spatial, thematic and bibliographical attributes. The final list of 137 publications indicates that, regionally, the Arctic has been covered more than the Antarctic, whilst an uneven distribution within the Arctic also exists. In terms of the climate change risks themes, climate risk research, i.e. impact and adaptation studies, strongly outnumbers the carbon risk studies especially in the Arctic context, and, despite a balance between the two main risk themes, climate risk research in the Antarctic proves itself outdated. Accordingly, the review ends with a research agenda based on these spatial and thematic gaps and their detailed breakdowns.
Publisher: Routledge
Keywords: Antarktis; bibliografi; geobibliografi; klimaendringer; polarområdene; turisme

Conjugate aurora observations by the Gjøa and Discovery expeditions - Egeland, Alv (Hist. Geo Space. Sci., 2024)
From 1901 to 1912 – known as the “heroic period” of Arctic and Antarctic exploration – great inroads were made (not only geographic but also scientific) to our knowledge of the continent. At Amundsen's Expedition through the Northwest Passage, measurements of the geomagnetic field and visual auroras were carried out for 19 months at Gjoa Haven (Gjøahavn in Norwegian; geographic coordinates 68°37′10′′ N, 95°53′25′′ W). Scott's Discovery Expedition – at Cape Armitage, McMurdo (coordinates 77.86° S, 166.69° E), Antarctica – carried out the same type of measurements. Their observations were carried out geomagnetically conjugate to Gjoa Haven, with both stations close to 78° magnetic latitude. In addition, measurements were overlapping in time during 1903–1904. However, these two stations are located at different longitudes, so there is a difference in local time between the stations of about 6.5 h. Gjoa Haven and Cape Armitage are conveniently located for separating disturbances in the polar cap regions caused by solar electromagnetic radiations or the solar wind. Auroras were observed during 7 months per year. This gave a unique possibility to compare conjugate characteristics of polar cap auroras. Comparing conjugate geophysical data introduces some difficulties. During the winter season at Gjoa Haven, they had a bright summer in Antarctica, and visa versa. Thus, simultaneous temporal and spatial ionospheric variations can be marked differently. Still, the average diurnal and seasonal variations were similar. The quantity of the auroral data from Cape Armitage was larger because there they had a continuous watch of the sky. The main findings regarding polar cap auroras are the following. Three different auroral forms dominate the polar cap. Low-intensity auroral bands – then called streamers – were the dominating auroral forms morning and afternoon. The number of auroral events in 1903 was nearly twice that in 1902 and 1904. A marked midwinter maximum was observed at both stations. Many displays were observed poleward of the oval. The large fraction was associated with weak magnetic disturbances. Some forms of polar cap aurora have special magnetic signatures and seem to be anti-correlated with Kp. They can be mapped even if they are not seen. According to recent satellite measurements (Newell et al., 2009), they are probably caused by polar rain and/or photoelectrons.
Publisher: Copernicus Publications
Keywords: Antarktis; Discoveryekspedisjonen; fysikk; polarfarere; polarområdene; romfysikk; sørlys

Short- and long-term variability of the Antarctic and Greenland ice sheets - Hanna, Edward; Topál, Dániel; Box, Jason E.; Buzzard, Sammie; Christie, Frazer D. W.; Hvidberg, Christine; Morlighem, Mathieu; De Santis, Laura; Silvano, Alessandro; Colleoni, Florence; Sasgen, Ingo; Banwell, Alison F.; et al. (Nature Reviews Earth & Environment, 2024)
The variability of the Antarctic and Greenland ice sheets occurs on various timescales and is important for projections of sea level rise; however, there are substantial uncertainties concerning future ice-sheet mass changes. In this Review, we explore the degree to which short-term fluctuations and extreme glaciological events reflect the ice sheets’ long-term evolution and response to ongoing climate change. Short-term (decadal or shorter) variations in atmospheric or oceanic conditions can trigger amplifying feedbacks that increase the sensitivity of ice sheets to climate change. For example, variability in ocean-induced and atmosphere-induced melting can trigger ice thinning, retreat and/or collapse of ice shelves, grounding-line retreat, and ice flow acceleration. The Antarctic Ice Sheet is especially prone to increased melting and ice sheet collapse from warm ocean currents, which could be accentuated with increased climate variability. In Greenland both high and low melt anomalies have been observed since 2012, highlighting the influence of increased interannual climate variability on extreme glaciological events and ice sheet evolution. Failing to adequately account for such variability can result in biased projections of multi-decadal ice mass loss. Therefore, future research should aim to improve climate and ocean observations and models, and develop sophisticated ice sheet models that are directly constrained by observational records and can capture ice dynamical changes across various timescales.
Keywords: Antarktis; glasiologi; innlandsis; klimaendringer; polarområdene

The Use of Weather, Water, Ice, and Climate (WWIC) Information in the Polar Regions: What Is Known after the Decadelong Polar Prediction Project? - Heinrich, Victoria J.; Stewart, Emma J.; Liggett, Daniela; Carrasco, Jorge F.; Dawson, Jackie; Lamers, Machiel; Ljubicic, Gita J.; Jeuring, Jelmer; Thoman, Rick (Weather, Climate, and Society, 2024)
The polar regions are facing a wide range of compounding challenges, from climate change to increased human activity. Infrastructure, rescue services, and disaster response capabilities are limited in these remote environments. Relevant and usable weather, water, ice, and climate (WWIC) information is vital for safety, activity success, adaptation, and environmental protection. This has been a key focus for the World Meteorological Organization’s (WMO) Polar Prediction Project (PPP), and in particular its “Societal and Economic Research and Applications” (PPP-SERA) Task Team, which together over a decade have sought to understand polar WWIC information use in relation to operational needs, constraints, and decision contexts to inform the development of relevant services. To understand research progress and gaps on WWIC information use during the PPP (2013–23), we undertook a systematic bibliometric review of aligned scholarly peer-reviewed journal articles (n = 43), examining collaborations, topics, methods, and regional differences. Themes to emerge included activity and context, human factors, information needs, situational awareness, experience, local and Indigenous knowledge, and sharing of information. We observed an uneven representation of disciplinary backgrounds, geographic locations, research topics, and sectoral foci. Our review signifies an overall lack of Antarctic WWIC services research and a dominant focus on Arctic sea ice operations and risks. We noted with concern a mismatch between user needs and services provided. Our findings can help to improve WWIC services’ dissemination, communication effectiveness, and actionable knowledge provision for users and guide future research as the critical need for salient weather services across the polar regions remains beyond the PPP. Significance Statement Every day, people in the Arctic and Antarctic use weather, water, ice, and climate information to plan and carry out outdoor activities and operations in a safe way. Despite advances in numerical weather prediction, technology, and product development, barriers to accessing and effectively communicating high-quality usable observations, forecasts, and actionable knowledge remain. Poorer services, prediction accuracy, and interpretation are exacerbated by a lack of integrated social science research on relevant topics and a mismatch between the services provided and user needs. As a result, continued user engagement, research focusing on information use, risk communication, decision-making processes, and the application of science for services remain highly relevant to reducing risks and improving safety for people living, visiting, and working in the polar regions.
Place: Boston MA, USA Publisher: American Meteorological Society
Keywords: Antarktis; klimaendringer; klimatologi; meteorologi; polarområdene

Arctic copepod copper sensitivity and comparison with Antarctic and temperate copepods - Heuschele, Jan; Dinh, Khuong V.; Lode, Torben; Jager, Tjalling; Borgå, Katrine (Ecotoxicology, 2024)
The ongoing global climate crisis increases temperatures in polar regions faster and with greater magnitude than elsewhere. The decline of Arctic sea ice opens up new passages, eventually leading to higher anthropogenic activities such as shipping, fishing, and mining. Climate change and anthropogenic activities will increase contaminant transport from temperate to Arctic regions. The shipping industry uses copper as an antifouling coating. Copper is an essential element but becomes toxic at excess concentrations, and its use may inadvertently affect non-target organisms such as copepods. Copper affects copepods by lowering reproductive output, prolonging developmental time, and causing increased mortality. As data on copper sensitivity of polar copepods at low temperatures are rare, we conducted onboard survival experiments with the Arctic region’s most common copepod species (Calanus finmarchicus, C. glacialis, C. hyperboreus). Acute survival tests were done for up to 8 days on individuals in 70 ml bottles at 1 °C with nominal copper concentrations ranging from 3 to 480 μg L−1. We used a reduced General Unified Threshold model for Survival (GUTS) to analyse the data, and placed our results in the context of the few published copper sensitivity data of the Antarctic and temperate copepod species at low temperatures. The sensitivity of Cu exposure was similar between the three Calanus species. However, a model comparison suggests that the tested C. glacialis population is less sensitive than the other two species in our experiments. Compared to published data, the three Arctic species appear slightly less sensitive to copper compared to their Antarctic counterparts but more compared to their temperate ones. Our literature search revealed only a few available studies on the copper sensitivity of polar copepods. In the future, this species group will be exposed to more pollutants, which warrants more studies to predict potential risks, especially given possible interactions with environmental factors.
Keywords: Antarktis; copepoder; forurensning; hoppekreps; klimaendringer; marin biologi; miljøgifter; polarområdene; økotoksikologi

Regional polar warming linked to poleward moisture transport variability - Bintanja, Richard; Graversen, Rune Grand; Kolbe, Marlen (Environmental Research: Climate, 2023)
Polar warming, ice melt and strong precipitation events are strongly affected by episodic poleward advection of warm and moist air (Woods and Caballero 2016 J. Clim. 29 4473–85; Wille et al 2019 Nat. Geosci. 12 911–6), which, in turn, is linked to variability in poleward moisture transport (PMT) (Nash et al 2018 J. Geophys. Res. Atmos. 123 6804–21). However, processes governing regional impacts of PMT as well as long-term trends remain largely unknown. Here we use an ensemble of state-of-the-art global climate models in standardized scenario simulations (1850–2100) to show that both the Arctic and the Antarctic exhibit distinct geographical patterns of PMT-related warming. Specifically, years with high PMT experience considerable warming over subarctic Eurasia and West-Antarctica (Raphael et al 2016 Bull. Am. Meteorol. Soc. 97 111–21), whereas precipitation is distributed more evenly over the polar regions. The warming patterns indicate preferred routes of atmospheric rivers (Woods and Caballero 2016 J. Clim. 29 4473–85), which may regionally enhance atmospheric moisture content, cloud cover, and downward longwave radiative heating in years with comparatively high PMT (Scott et al 2019 J. Clim. 32 665–84). Trend-analyses reveal that the link between PMT-variability and regional precipitation patterns will weaken in both polar regions. Even though uncertainties associated with intermodel differences are considerable, the advection of warm and moist air associated with PMT-variability is likely to increasingly cause mild conditions in both polar regions, which in the Arctic will reinforce sea-ice melt. Similarly, the results suggest that warm years in West-Antarctica disproportionally contribute to ice sheet melt (Trusel et al 2015 Nat. Geosci. 8 927–32), enhancing the risk of ice-sheet instabilities causing accelerated and sudden sea-level rise.
Publisher: IOP Publishing
Keywords: Antarktis; global oppvarming; klimamodeller; meteorologi; polarområdene

Strong and lasting impacts of past global warming on baleen whales and their prey - Cabrera, Andrea A; Schall, Elena; Bérubé, Martine; Anderwald, Pia; Bachmann, Lutz; Berrow, Simon; Best, Peter B; Clapham, Phillip J; Cunha, Haydée A.; Dalla Rosa, Luciano; Dias, Carolina; Findlay, Kenneth P.; et al. (Global Change Biology, 2022)
Global warming is affecting the population dynamics and trophic interactions across a wide range of ecosystems and habitats. Translating these real-time effects into their long-term consequences remains a challenge. The rapid and extreme warming period that occurred after the Last Glacial Maximum (LGM) during the Pleistocene–Holocene transition (7–12 thousand years ago) provides an opportunity to gain insights into the long-term responses of natural populations to periods with global warming. The effects of this post-LGM warming period have been assessed in many terrestrial taxa, whereas insights into the impacts of rapid global warming on marine taxa remain limited, especially for megafauna. In order to understand how large-scale climate fluctuations during the post-LGM affected baleen whales and their prey, we conducted an extensive, large-scale analysis of the long-term effects of the post-LGM warming on abundance and inter-ocean connectivity in eight baleen whale and seven prey (fish and invertebrates) species across the Southern and the North Atlantic Ocean; two ocean basins that differ in key oceanographic features. The analysis was based upon 7032 mitochondrial DNA sequences as well as genome-wide DNA sequence variation in 100 individuals. The estimated temporal changes in genetic diversity during the last 30,000 years indicated that most baleen whale populations underwent post-LGM expansions in both ocean basins. The increase in baleen whale abundance during the Holocene was associated with simultaneous changes in their prey and climate. Highly correlated, synchronized and exponential increases in abundance in both baleen whales and their prey in the Southern Ocean were indicative of a dramatic increase in ocean productivity. In contrast, the demographic fluctuations observed in baleen whales and their prey in the North Atlantic Ocean were subtle, varying across taxa and time. Perhaps most important was the observation that the ocean-wide expansions and decreases in abundance that were initiated by the post-LGM global warming, continued for millennia after global temperatures stabilized, reflecting persistent, long-lasting impacts of global warming on marine fauna.
Keywords: Sørishavet; klimaendringer; marin biologi; polarområdene

Allometric relationships of ecologically important Antarctic and Arctic zooplankton and fish species - Schaafsma, Fokje L.; David, Carmen L.; Kohlbach, Doreen; Ehrlich, Julia; Castellani, Giulia; Lange, Benjamin A.; Vortkamp, Martina; Meijboom, André; Fortuna-Wünsch, Anna; Immerz, Antonia; Cantzler, Hannelore; Klasmeier, Apasiri; et al. (Polar Biology, 2022)
Allometric relationships between body properties of animals are useful for a wide variety of purposes, such as estimation of biomass, growth, population structure, bioenergetic modelling and carbon flux studies. This study summarizes allometric relationships of zooplankton and nekton species that play major roles in polar marine food webs. Measurements were performed on 639 individuals of 15 species sampled during three expeditions in the Southern Ocean (winter and summer) and 2374 individuals of 14 species sampled during three expeditions in the Arctic Ocean (spring and summer). The information provided by this study fills current knowledge gaps on relationships between length and wet/dry mass of understudied animals, such as various gelatinous zooplankton, and of animals from understudied seasons and maturity stages, for example, for the krill Thysanoessa macrura and larval Euphausia superba caught in winter. Comparisons show that there is intra-specific variation in length–mass relationships of several species depending on season, e.g. for the amphipod Themisto libellula. To investigate the potential use of generalized regression models, comparisons between sexes, maturity stages or age classes were performed and are discussed, such as for the several krill species and T. libellula. Regression model comparisons on age classes of the fish E. antarctica were inconclusive about their general use. Other allometric measurements performed on carapaces, eyes, heads, telsons, tails and otoliths provided models that proved to be useful for estimating length or mass in, e.g. diet studies. In some cases, the suitability of these models may depend on species or developmental stages.
Keywords: Sørishavet; biomasse; dyreplankton; fisker; marin biologi; marin økologi; polarområdene; zooplankton

Spatial and interspecific variation of accumulated highly toxic trace elements between fifteen bird species feathers from Antarctic, Arctic and China - Sun, Yayue; Lu, Zhibo; Xiao, Kaiyan; Zeng, Lingyun; Wang, Juan; Zhang, Yanyun; Gabrielsen, Geir Wing (Environmental Technology & Innovation, 2022)
To assess the impact of human activities and other factors on the levels of highly toxic trace elements in the environment, the contents of eight highly toxic trace elements (arsenic (As), cadmium (Cd), chromium (Cr), copper (Cu), mercury (Hg), nickel (Ni), lead (Pb) and zinc (Zn)) in feathers of 15 bird species from the Prydz Bay region in the Antarctic, Ny-Alsund region in the Arctic, and eastern China were evaluated in this study. Results showed that feathers collected from the Antarctic showed the highest As, Cu, and Hg contents (1.65–2.85, 9.58–18.56, and 4.77–8.76 μg/g dw, respectively) of the different study areas, whereas Arctic feathers exhibited the highest mean Pb levels (1.82–3.19 μg/g dw), and feathers from China showed significantly lower accumulations of Cr, Ni, Pb, and Zn compared with the other two areas. Overall, most of the studied highly toxic trace element contents in bird feathers from the densely populated and polluted area of eastern China were lower than those from remote polar regions, which are negligibly affected by human activities. In addition, feathers from the Arctic did not show higher highly toxic trace element contents than those of the more remote Antarctic. These results are thus inferred to reflect differences in the dietary structure of birds in the different habitats, as well as historical climate change. Carbon (δ13C) and nitrogen (δ15N) stable isotope ratios of feathers were also measured to evaluate the relationship between diet and highly toxic trace elements. Results showed that highly toxic trace element contents did not increase with increasing trophic levels. Moreover, the methylmercury content accounted for 87.57%–98.59% of the total mercury in all feather samples, regardless of location and species, confirming that most of the mercury entering the feathers is methylated. This finding suggests that the form of mercury changes during the process of transference from internal tissues to feathers, which improves our understanding of the mechanism by which feathers excrete mercury, this behavior greatly reduces the harm to bird health caused by mercury. This study confirms that measuring contaminants in feathers is a long-term and effective method for monitoring highly toxic trace elements pollution in particular environments, making future monitoring of highly toxic trace elements pollution in the polar regions, as well as more typical environments, more convenient.
Keywords: Antarktis; miljøgifter; polarområdene; sjøfugler; økotoksikologi

First discrete iron(II) records from Dome C (Antarctica) and the Holtedahlfonna glacier (Svalbard) - Burgay, François; Barbaro, Elena; Cappelletti, David; Turetta, Clara; Gallet, Jean-Charles; Isaksson, Elisabeth; Stenni, Barbara; Dreossi, Giuliano; Scoto, Federico; Barbante, Carlo; Spolaor, Andrea (Chemosphere, 2021)
Fe(II) is more soluble and bioavailable than Fe(III) species, therefore the investigation of their relative abundance and redox processes is relevant to better assess the supply of bioavailable iron to the ocean and its impact on marine productivity. In this context, we present a discrete chemiluminescence-based method for the determination of Fe(II) in firn matrices. The method was applied on discrete samples from a snow pit collected at Dome C (DC, Antarctica) and on a shallow firn core from the Holtedahlfonna glacier (HDF, Svalbard), providing the first Fe(II) record from both Antarctica and Svalbard. The method showed low detection limits (0.006 ng g−1 for DC and 0.003 ng g−1 for the HDF) and a precision ranging from 3% to 20% RSD. Fe(II) concentrations ranged between the LoD and 0.077 ng g−1 and between the LoD and 0.300 ng g−1 for the Antarctic and Arctic samples, respectively. The Fe(II) contribution with respect to the total dissolved Fe was comparable in both sites accounting, on average, for 5% and 3%, respectively. We found that Fe(II) correctly identified the Pinatubo/Cerro Hudson eruption in the DC record, demonstrating its reliability as volcanic tracer, while, on the HDF core, we provided the first preliminary insight on the processes that might influence Fe speciation in firn matrices (i.e. organic ligands and pH influences).
Keywords: Antarktis; glasiologi; kjemi; polarområdene

Projected land ice contributions to twenty-first-century sea level rise - Edwards, Tamsin L; Nowicki, Sophie; Marzeion, Ben; Hock, Regine; Goelzer, Heiko; Seroussi, Hélène; Jourdain, Nicolas C; Slater, Donald A; Turner, Fiona E; Smith, Christopher J; McKenna, Christine M; Simon, Erika; et al. (Nature, 2021)
The land ice contribution to global mean sea level rise has not yet been predicted using ice sheet and glacier models for the latest set of socio-economic scenarios, nor using coordinated exploration of uncertainties arising from the various computer models involved. Two recent international projects generated a large suite of projections using multiple models, but primarily used previous-generation scenarios and climate models, and could not fully explore known uncertainties. Here we estimate probability distributions for these projections under the new scenarios using statistical emulation of the ice sheet and glacier models. We find that limiting global warming to 1.5 degrees Celsius would halve the land ice contribution to twenty-first-century sea level rise, relative to current emissions pledges. The median decreases from 25 to 13 centimetres sea level equivalent (SLE) by 2100, with glaciers responsible for half the sea level contribution. The projected Antarctic contribution does not show a clear response to the emissions scenario, owing to uncertainties in the competing processes of increasing ice loss and snowfall accumulation in a warming climate. However, under risk-averse (pessimistic) assumptions, Antarctic ice loss could be five times higher, increasing the median land ice contribution to 42 centimetres SLE under current policies and pledges, with the 95th percentile projection exceeding half a metre even under 1.5 degrees Celsius warming. This would severely limit the possibility of mitigating future coastal flooding. Given this large range (between 13 centimetres SLE using the main projections under 1.5 degrees Celsius warming and 42 centimetres SLE using risk-averse projections under current pledges), adaptation planning for twenty-first-century sea level rise must account for a factor-of-three uncertainty in the land ice contribution until climate policies and the Antarctic response are further constrained.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi; polarområdene; smelting

Evaluation of interannual variability of Arctic and Antarctic ozone loss since 1989 - Goutail, Florence; Pazmino, Andrea; Pommereau, Jean-Pierre; Lefèvre, Franck; Godin-Beekmann, Sophie; Hauchecorne, Alain; Lecouffe, Audrey; Clerbaux, Cathy; Boynard, Anne; Hadji-Lazaro, Juliette; Chipperfield, Martyn; Feng, Wuhu; et al. (2021)
Ozone depletion over Polar Regions is monitored each year by satellite and ground-based instruments. The first signs of healing of the ozone layer linked to the decrease of ozone destructive substances (ODSs) were observed in Antarctica using different metrics (ozone mean values, ozone mass deficit, area of the ozone hole) and simple or sophisticated models. Chemistry climate models predict that climate change will not affect expected ozone recovery over Antarctica but will accelerate recovery in the Arctic due to the possible enhancement of the Brewer Dobson circulation. However, ozone loss observations by SAOZ UV-Vis spectrometers do not show a clear sign of recovery in the latter region. In addition, a record of 38% ozone loss in 2010/2011 and 2019/2020 was estimated. In this study, the vortex-averaged ozone loss in the last three decades will be evaluated for both Polar Regions using the passive ozone tracer of two chemical transport models (REPROBUS and SLIMCAT CTMs) and total ozone observations from SAOZ and satellite observations (IASI/METOP and Multi-Sensor Reanalysis (MSR-2)). The tracer method allows us to determine the evolution of the daily rate of ozone destruction, and the amplitude of the cumulative loss at the end of the winter. The cumulative ozone destruction in the Artic varies between 0-10% in relatively warm winters with short vortex duration to up to 25-38% in colder winters with longer vortex persistence, while in Antarctica it is mostly stable, around 50%. Interannual variability of 10-days average rate will be analyzed and compared between both hemispheres as well as the timing to reach different thresholds of absolute ozone loss values. Finally, linear trend of ozone loss and temperature since 2000 will be estimated in both Polar Regions in order to evaluate possible ozone recovery.
Publication Title: EGU General Assembly 2021 Place: Online, Germany
Keywords: Antarktis; klimaendringer; miljøovervåking; ozonlaget; polarområdene

Case Study of Blowing Snow Impacts on the Antarctic Peninsula Lower Atmosphere and Surface Simulated With a Snow/Ice Enhanced WRF Model - Luo, Liping; Zhang, Jing; Hock, Regine; Yao, Yao (Journal of Geophysical Research: Atmospheres, 2021)
To better capture the air-snow-ice interaction, a snow/ice enhanced Weather Research and Forecasting (WRF-ice) model has been developed. This study examines the performance of WRF-ice and its blowing snow component during a strong cyclone event from October 23 to 27, 2017 over the Antarctic Peninsula, which is characterized by a synoptic cyclone crossing the northern part of the Peninsula and an embodied mesoscale cyclone over the Weddell Sea. Evolution of the cyclone is accurately reproduced in the 5-km resolution WRF-ice simulation, and the simulated near-surface conditions agree well with station and satellite observations. Numerical simulations show that the process of blowing snow sublimation can be prominent within the lower atmosphere when the air is dry, and produces moistening and cooling effects. Over relatively warm and humid areas, cloud enhancement by blowing snow can lead to either colder or warmer surfaces because of competing effects of longwave and shortwave cloud radiative forcings. In particular, additional moisture from blowing snow sublimation can slightly intensify precipitation over the mountains. Surface energy budget analysis indicates that absorbed shortwave (Sa), incoming longwave (Ld), and outgoing longwave (Lu) are dominant components of surface energy budget. When increases in Ld, Lu, and sensible heat flux are combined with decreases in Sa and latent heat flux due to blowing snow effects, a negative surface net heat flux (∼0.5 W/m2) occurs during daytime. A positive domain-total surface mass balance (∼0.43 Gt) is generated during the simulated cyclone event due to increases in precipitation, decreases in runoff, and decreases in sublimation.
Keywords: Antarktis; akkumulasjon; atmosfæren; geofysikk; geovitenskap; is; meteorologi; polarområdene; satellite; snø

Quantarctica, an integrated mapping environment for Antarctica, the Southern Ocean, and sub-Antarctic islands - Matsuoka, Kenichi; Skoglund, Anders; Roth, George; de Pomereu, Jean; Griffiths, Huw; Headland, Robert; Herried, Brad; Katsumata, Katsuro; Le Brocq, Anne; Licht, Kathy; Morgan, Fraser; Neff, Peter D; et al. (Environmental Modelling & Software, 2021)
Quantarctica (https://www.npolar.no/quantarctica) is a geospatial data package, analysis environment, and visualization platform for the Antarctic Continent, Southern Ocean (>40oS), and sub-Antarctic islands. Quantarctica works with the free, cross-platform Geographical Information System (GIS) software QGIS and can run without an Internet connection, making it a viable tool for fieldwork in remote areas. The data package includes basemaps, satellite imagery, terrain models, and scientific data in nine disciplines, including physical and biological sciences, environmental management, and social science. To provide a clear and responsive user experience, cartography and rendering settings are carefully prepared using colour sets that work well for typical data combinations and with consideration of users with common colour vision deficiencies. Metadata included in each dataset provides brief abstracts for non-specialists and references to the original data sources. Thus, Quantarctica provides an integrated environment to view and analyse multiple Antarctic datasets together conveniently and with a low entry barrier.
Keywords: Antarktis; Sørishavet; geografi; kartografi; polarområdene

Cancellation of the Precessional Cycle in δ18O Records During the Early Pleistocene - Morée, Anne L; Sun, Tianyi; Bretones, Anaïs; Straume, Eivind O; Nisancioglu, Kerim; Gebbie, Geoffrey (Geophysical Research Letters, 2021)
The dominant pacing of glacial-interglacial cycles in deep-ocean δ18O records changed substantially during the Mid-Pleistocene Transition. The precessional cycle (∼23 ky) is absent during the Early Pleistocene, which we show can be explained by cancellation of the hemispherically antiphased precessional cycle in the Early Pleistocene interior ocean. Such cancellation develops due to mixing of North Atlantic and Southern Ocean δ18O signals at depth, and shows characteristic spatial patterns. We explore the cancellation potential for different North Atlantic and Southern Ocean deep-water source δ18O values using a tracer transport ocean model. Cancellation of precession occurs for all signal strengths and is widespread for a signal strength typical for the Early Pleistocene. Early Pleistocene precessional power is therefore likely incompletely archived in deep-sea δ18O records, concealing the true periodicity of the glacial cycles in the two hemispheres.
Keywords: Sørishavet; geofysikk; innlandsis; oseanografi; paleontologi; polarområdene

Future sea level change under CMIP5 and CMIP6 scenarios from the Greenland and Antarctic ice sheets - Payne, Antony J; Nowicki, Sophie; Abe-Ouchi, Ayako; Agosta, Cécile; Alexander, Patrick; Albrecht, Torsten; Asay-Davis, Xylar; Aschwanden, Andy; Barthel, Alice; Bracegirdle, Thomas J; Calov, Reinhard; Chambers, Christopher; et al. (Geophysical Research Letters, 2021)
Projections of the sea level contribution from the Greenland and Antarctic ice sheets rely on atmospheric and oceanic drivers obtained from climate models. The Earth System Models participating in the Coupled Model Intercomparison Project phase 6 (CMIP6) generally project greater future warming compared with the previous CMIP5 effort. Here we use four CMIP6 models and a selection of CMIP5 models to force multiple ice sheet models as part of the Ice Sheet Model Intercomparison Project for CMIP6 (ISMIP6). We find that the projected sea level contribution at 2100 from the ice sheet model ensemble under the CMIP6 scenarios falls within the CMIP5 range for the Antarctic ice sheet but is significantly increased for Greenland. Warmer atmosphere in CMIP6 models results in higher Greenland mass loss due to surface melt. For Antarctica, CMIP6 forcing is similar to CMIP5 and mass gain from increased snowfall counteracts increased loss due to ocean warming.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi; polarområdene; smelting

Hvordan vet vi det vi vet om global oppvarming? - Seip, Knut Lehre (Naturen, 2021)
Hvordan vet vi det vi vet om global oppvarming? Denne artikkelen diskuterer grunnlaget for det vi vet med stor sikkerhet. I artikkelen diskuterer vi 12 temaer, og velger ut én eller to metoder som illustrerer hvordan kunnskap er skaffet til veie for hvert av temaene.
Keywords: Antarktis; global oppvarming; klimaendringer; klimatologi; polarområdene

Satellite and ground based estimates for ice surface velocities in the part of central Dronning Maud Land, East Antarctica: Implications for ice flux calculations - Thakur, Praveen K; Swain, Ashit K; Dhote, Pankaj R; Kumar, Pradeep; Kaushik, Suvrat; Gajbhiye, Deepak; Mahagaonkar, Anirudha; Sharma, Vishal; Dharwadkar, Amit; Aggarwal, S P; Beg, Javed; Chauhan, Prakash; et al. (Polar Science, 2021)
The ice sheet and glaciers of Antarctica and Greenland represent the largest sources of freshwater on planet Earth. The understanding and quantification of their dynamic properties such as albedo, precipitation, ice mass movement, and ice elevation changes are critical for the improved climate and mass balance models. The present study utilizes space-borne optical and synthetic aperture radar (SAR) imagery to measure the ice surface velocity at high spatial resolution for a part of the central Dronning Maud Land (cDML), East Antarctica. The datasets from Landsat-8 and Sentinel-1 SAR satellite are used for ice stream velocity estimation using feature-offset tracking and differential interferometric SAR (DInSAR) methods. The derived velocity products are validated with ground based stakes network at annual time scale. The fundamental ice flow laws are used to estimate the ice outflux or discharge for selected ice stream drainage basins of cDML at fluxgate locations. The ice stream basin has been delineated using combination of elevation, slope and continental scale velocity maps. The ice influx for study area is estimated using ECMWF fifth generation reanalysis (ERA5) and Regional Atmospheric Climate Model (RACMO) v2.3 model outputs. The estimated influx and outflux are in the ranges of 0.18–4.167 Gt/y and 0.201 to 1.278 Gt/y respectively, indicating net positive mass balance for the selected area.
Keywords: Dronning Maud Land; glasiologi; innlandsis; polarområdene

Full-Depth Global Estimates of Ocean Mesoscale Eddy Mixing From Observations and Theory - Groeskamp, Sjoerd; LaCasce, Joseph H; McDougall, Trevor J; Rogé, Marine (Geophysical Research Letters, 2020)
Mixing by mesoscale eddies profoundly impacts climate and ecosystems by redistributing and storing dissolved tracers such as heat and carbon. Eddy mixing is parameterized in most numerical models of the ocean and climate. To reduce known sensitivity to such parameterizations, observational estimates of mixing are needed. However, logistical and technological limitations obstruct our ability to measure global time-varying mixing rates. Here, we extend mixing length theory with mean-flow suppression theory, and first surface modes, to estimate mixing from readily available observational-based climatological data, of salinity, temperature, pressure, and eddy kinetic energy at the sea surface. The resulting full-depth global maps of eddy mixing can reproduce the few available direct estimates and confirm the importance of mean-flow suppression of mixing. The results also emphasize the significant effect of eddy surface intensification and its relation to the vertical density stratification. These new insights in mixing dynamics will improve future mesoscale eddy mixing parameterizations.
Keywords: Sørishavet; geovitenskap; havet; klimatologi; polarområdene; vannvirvler; økosystemer

Supercooled Southern Ocean Waters - Haumann, F Alexander; Moorman, Ruth; Riser, Stephen C; Smedsrud, Lars H; Maksym, Ted; Wong, Annie P S; Wilson, Earle A; Drucker, Robert; Talley, Lynne D; Johnson, Kenneth S; Key, Robert M; Sarmiento, Jorge L (Geophysical Research Letters, 2020)
In cold polar waters, temperatures sometimes drop below the freezing point, a process referred to as supercooling. However, observational challenges in polar regions limit our understanding of the spatial and temporal extent of this phenomenon. We here provide observational evidence that supercooled waters are much more widespread in the seasonally ice-covered Southern Ocean than previously reported. In 5.8% of all analyzed hydrographic profiles south of 55°S, we find temperatures below the surface freezing point (“potential” supercooling), and half of these have temperatures below the local freezing point (“in situ” supercooling). Their occurrence doubles when neglecting measurement uncertainties. We attribute deep coastal-ocean supercooling to melting of Antarctic ice shelves and surface-induced supercooling in the seasonal sea-ice region to wintertime sea-ice formation. The latter supercooling type can extend down to the permanent pycnocline due to convective sinking plumes—an important mechanism for vertical tracer transport and water-mass structure in the polar ocean.
Keywords: Sørishavet; havis; hydrografi; isbrem; isshelf; oseanografi; polarområdene; sjøis; superkjøling

Interhemispheric Asymmetry of Large-Scale Electron Density Gradients in the Polar Cap Ionosphere: UT and Seasonal Variations - Jin, Yaqi; Xiong, Chao (Journal of Geophysical Research: Space Physics, 2020)
The high-latitude ionosphere is highly dynamical with significant irregularities and density gradients. However, the spatial and temporal distributions of density gradients and irregularities are very different between the Arctic and Antarctic. In this report, we study the interhemispheric asymmetry of the large-scale (100 km) density gradients in both polar caps. Our results show that density gradients in the Arctic are enhanced during local winter (December solstice) with a peak around 19 UT. The UT and spatial distributions in the Antarctic local winter (June solstice) are similar to the Arctic except that they are reversed by 12 hr, which indicates a mirror symmetry between hemispheres. The 12-hr difference in the peak density gradients can be explained by the displacements between the geographic and geomagnetic poles. The only asymmetry (anomaly) is the persistence of strong density gradients in the southern polar cap during local summer (December solstice).
Keywords: Antarktis; fysikk; geovitenskap; ionosfæren; polarområdene

CloudSat-Inferred Vertical Structure of Snowfall Over the Antarctic Continent - Lemonnier, Florentin; Madeleine, Jean-Baptiste; Claud, Chantal; Palerme, Cyril; Genthon, Christophe; L'Ecuyer, Tristan; Wood, Norman B (Journal of Geophysical Research: Atmospheres, 2020)
Current global warming is causing significant changes in snowfall in polar regions, directly impacting the mass balance of the ice caps. The only water supply in Antarctica, precipitation, is poorly estimated from surface measurements. The onboard cloud-profiling radar of the CloudSat satellite provided the first real opportunity to estimate solid precipitation at continental scale. Based on CloudSat observations, we propose to explore the vertical structure of precipitation in Antarctica over the 2007–2010 period. A first division of this data set following a topographical approach (continent vs. peripheral regions, with a 2,250 m topographical criterion) shows a high snowfall rate (275 mm yr at 1,200 m above ground level) with low relative seasonal variation ( ) over the peripheral areas. Over the plateau, the snowfall rate is low (34 mm yr at 1,200 m above ground level) with a much larger relative seasonal variation ( ). A second study that follows a geographical division highlights the average vertical structure of precipitation and temperature depending on the regions and their interactions with topography. In particular, over ice shelves, we see a strong dependence of the distribution of snowfall on the sea ice coverage. Finally, the relationship between precipitation and temperature is analyzed and compared with a simple analytical relationship. This study highlights that precipitation is largely dependent on the advection of air masses along the topographic slopes with an average vertical wind of 0.02 m s . This provides new diagnostics to evaluate climate models with a three-dimensional approach of the atmospheric structure of precipitation.
Keywords: Antarktis; global oppvarming; klimamodeller; klimatologi; meteorologi; nedbør; polarområdene; snøfall

Will Climate Change Impact Polar NOx Produced by Energetic Particle Precipitation? - Maliniemi, Ville; Marsh R., Daniel; Tyssøy, Hilde Nesse; Smith-Johnsen, Christine (Geophysical Research Letters, 2020)
Energetic electron precipitation (EEP) is an important source of polar nitrogen oxides (NOx) in the upper atmosphere. During winter, mesospheric NOx has a long chemical lifetime and is transported to the stratosphere by the mean meridional circulation. Climate change is expected to accelerate this circulation and therefore increase polar mesospheric descent rates. We investigate the Southern Hemispheric polar NOx distribution during the 21st century under a variety of future scenarios using simulations of the Whole Atmosphere Community Climate Model (WACCM). We simulate stronger polar mesospheric descent in all future scenarios that increase the atmospheric radiative forcing. Polar NOx in the upper stratosphere is significantly enhanced in two future scenarios with the largest increase in radiative forcing. This indicates that the ozone depleting NOx cycle will become more important in the future, especially if stratospheric chlorine species decline. Thus, EEP-related atmospheric effects may become more prominent in the future.
Keywords: Antarktis; geofysikk; klimaendringer; klimatologi; ozonlaget; polarområdene; romvitenskap